Workplace Friendships : Examining Friendships at Work and Their Impact on Job Satisfaction and Perceived Productivity - Jones, Marissa; Stromberger, Jenna; Pape, Elizabeth; Chapman, Kelsey; Borremans, Adam (My University, 2014)
The purpose of this study was to investigate the perceived relationship between workplace friendship and productivity.
Color poster with text and images.
Keywords: Workplace; Friendship; Productivity; Posters